2014
DOI: 10.5603/cj.a2013.0154
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral vitamin C on atrial fibrillation development after isolated coronary artery bypass grafting surgery: A prospective randomized clinical trial

Abstract: C and control groups, respectively (p = 0.002). The hospital stay was significantly lower in vitamin C group compared with that of the control group (5.32 ± 0.59 vs. 5.74 ± 1.30 days, respectively, p = 0.041). Baseline erythrocyte sedimentation rate (OR 1.030, p = 0.030) and taking vitamin C (OR 8.068, p = 0.007) were the independent predictors of postoperative AF. Conclusions: Oral vitamin C can be safely used to decrease the incidence of postoperative AF in patients undergoing elective isolated on-pump CAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…The proportion of males varied from 58% to 75%. Five trials were carried out in Iran [12,13,15,18,19], two in Egypt [14,16], one in the USA [11], and one in Japan [17]. For detailed descriptions of the trials, see Additional file 1: Table S1.…”
Section: Results Of the Included Trialsmentioning
confidence: 99%
See 3 more Smart Citations
“…The proportion of males varied from 58% to 75%. Five trials were carried out in Iran [12,13,15,18,19], two in Egypt [14,16], one in the USA [11], and one in Japan [17]. For detailed descriptions of the trials, see Additional file 1: Table S1.…”
Section: Results Of the Included Trialsmentioning
confidence: 99%
“…Figure 4 indicates that the substantial benefit observed in that trial may be explained by the particularly sick patients with burns requiring very long ventilation, rather than by the very high vitamin C dose. We found that vitamin C shortened the length of ventilation on average by 25% (P = 10 −10 ) when the Tanaka trial was excluded and the analysis was restricted to the five trials with dosage from 1 to 6 g/day for patients ventilated for over 10 h [11,[13][14][15]18]. The Sadeghpour trial [19] is not included in our statistical models because of the high dropout rate, but the results are shown in Fig.…”
Section: Results Of the Included Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Dehghani et al [24] noted a role of oral vitamin C in the prevention of AF after CABG. These data support the inflammatory/ /oxidative stress pathophysiology of postoperative arrhythmia.…”
Section: Discussionmentioning
confidence: 99%